A direct dark matter search in XMASS-I - K. Abe; K. Hiraide; K. Ichimura; Y. Kishimoto; K. Kobayashi; M. Kobayashi; S. Moriyama; M. Nakahata; T. Norita; H. Ogawa; K. Sato; H. Sekiya; et al. (Physics Letters B, 2019)
A search for dark matter using an underground single-phase liquid xenon detector was conducted at the Kamioka Observatory in Japan, particularly for Weakly Interacting Massive Particles (WIMPs). We have used 705.9 live days of data in a fiducial volume containing 97kg of liquid xenon at the center of the detector. The event rate in the fiducial volume after the data reduction was (4.2±0.2)×10−3day−1kg−1keVee−1 at 5keVee, with a signal efficiency of 20%. All the remaining events are consistent with our background evaluation, mostly of the “mis-reconstructed events” originated from 210Pb in the copper plates lining the detector's inner surface. The obtained upper limit on a spin-independent WIMP-nucleon cross section was 2.2×10−44cm2 for a WIMP mass of 60GeV/c2 at the 90% confidence level, which was the most stringent limit among results from single-phase liquid xenon detectors. Keywords: Dark matter, Low background, Liquid xenon